Positive crosstalk between EGFR and the TF-PAR2 pathway mediates resistance to cisplatin and poor survival in cervical cancer - Hugo de Almeida, Vitor (Oncotarget, 2018)
Cisplatin-based chemoradiation is the standard treatment for cervical cancer, but chemosensitizing strategies are needed to improve patient survival. EGFR (Epidermal Growth Factor Receptor) is an oncogene overexpressed in cervical cancer that is involved in chemoresistance. Recent studies showed that EGFR upregulates multiple elements of the coagulation cascade, including tissue factor (TF) and the protease-activated receptors (PAR) 1 and 2. Moreover, many G protein-coupled receptors, including PARs, have been implicated in EGFR transactivation. However, the role of coagulation proteins in the progression of cervical cancer has been poorly investigated. Herein we employed cervical cancer cell lines and The Cancer Genome Atlas (TCGA) database to evaluate the role of EGFR, TF and PAR2 in chemoresistance. The SLIGKL-NH2 peptide (PAR2-AP) and coagulation factor VIIa (FVIIa) were used as PAR2 agonists, while cetuximab was used to inhibit EGFR. The more aggressive cell line CASKI showed higher expression levels of EGFR, TF and PAR2 than that of C33A. PAR2 transactivated EGFR, which further upregulated cyclooxygenase-2 (COX2) expression. PAR2-AP decreased cisplatin-induced apoptosis through an EGFR- and COX2-dependent mechanism. Furthermore, treatment of CASKI cells with EGF upregulated TF expression, while treatment with cetuximab decreased the TF protein levels. The RNA-seq data from 309 TCGA samples showed a strong positive correlation between EGFR and TF expression (P = 0.0003). In addition, the increased expression of EGFR, PAR2 or COX2 in cervical cancer patients was significantly correlated with poor overall survival. Taken together, our results suggest that EGFR and COX2 are effectors of the TF/FVIIa/PAR2 signaling pathway, promoting chemoresistance.